2000
DOI: 10.1088/0964-1726/9/1/303
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the acousto-ultrasonic transfer characteristics of adhesively bonded piezoceramic transducers

Abstract: For the development of optimised health monitoring systems and smart materials, the understanding of the interaction of piezoelectric transmitting and receiving transducers with the structure is essential. This paper reports on the development of an experimental technique to determine the acousto-ultrasonic transfer characteristics of adhesively bonded piezoceramic transducers. Five millimeter diameter piezoceramic discs with and without brass backing were glued to one and two millimeter thick aluminium plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Although special properties of these points have been well known since the early studies of dispersion of guided waves in plates and cylinders, they have been exploited only recently for material characterization and dynamic response studies. Recent experimental studies (Clorennec et al, 2007;Gibson and Popovics, 2005;Holland and Chimenti, 2004;Veidt et al, 2000) have shown that strong resonances occur in plates at frequencies where the group velocities of S 1 and A 2 modes vanish, but the phase velocities have finite values, i.e., the dispersion curves for those modes have minima below the cut-off frequencies. Since the group velocity of such a mode vanishes at the minimum, mechanical energy is trapped and high amplitude standing waves (vibrations) are present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although special properties of these points have been well known since the early studies of dispersion of guided waves in plates and cylinders, they have been exploited only recently for material characterization and dynamic response studies. Recent experimental studies (Clorennec et al, 2007;Gibson and Popovics, 2005;Holland and Chimenti, 2004;Veidt et al, 2000) have shown that strong resonances occur in plates at frequencies where the group velocities of S 1 and A 2 modes vanish, but the phase velocities have finite values, i.e., the dispersion curves for those modes have minima below the cut-off frequencies. Since the group velocity of such a mode vanishes at the minimum, mechanical energy is trapped and high amplitude standing waves (vibrations) are present.…”
Section: Introductionmentioning
confidence: 99%
“…The same concept has been used to refine another NDT method called 'Impact Test' (Gibson and Popovics, 2005) or traditional transducer excitation for nondestructive evaluation of composite plates (Veidt et al, 2000). In these, the normal displacements of a plate structure are measured after an impact or a force is applied to the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Model for 3-3 APT to solve for the excited GW field in isotropic platesEquating Eqs (30). and(31) would give three equations in four unknowns. The fourth equation results from the divergence condition on Η, and consequently, Η , given by:(28) in (32) and evaluating at 3…”
mentioning
confidence: 99%
“…The importance of the adhesive layer between a transducer and the structure was alluded to by Veidt et al (2000) who showed that the transfer of energy from transducer to specimen is a frequency dependent characteristic of the adhesive layer. Stating that changes to the transfer characteristics between the transducer and specimen that arise from the effects of temperature, moisture or component ageing may jeopardise the reliability of the system.…”
Section: 142mentioning
confidence: 99%